Thrombin generation and procoagulant microparticle profiles after acute trauma: A prospective cohort study. Issue 5 (November 2015) - Park, Myung S.; Xue, Ailing; Spears, Grant M.; Halling, Timothy M.; Ferrara, Michael J.; Kuntz, Melissa M.; Dhillon, Sabtir K.; Jenkins, Donald H.; Harmsen, William S.; Ballman, Karla V.; Harrison, Paul; Heit, John A.
Abstract : OBJECTIVE: The two sides of trauma-induced coagulopathy, the hypocoagulable and the hypercoagulable states, are poorly understood. To identify potential mechanisms for venous thromboembolism and bleeding after acute trauma, we estimated changes in circulating procoagulant microparticles (MPs) and thrombin activity during hospitalization for trauma. METHODS: Whole blood was collected by venipuncture into 3.2% trisodium citrate at 0, 6, 12, 24, and 72 hours after injury and discharge. Platelet-poor plasma was harvested and stored at −80°C until analysis. Thrombin generation was determined using the calibrated automated thrombogram (CAT), reported as lag time (minutes), peak height (nM thrombin), and time to reach peak height (ttPeak, minutes). The concentration of total procoagulant MPs (number/μL) was measured by flow cytometry. Data are presented as median (interquartile range [IQR]). RESULTS: Among 443 trauma patients (1, 734 samples; Injury Severity Score [ISS], 13.0 [IQR, 6.0–22.0]; hospital length of stay, 4.0 days [IQR, 2.0–10.0]; age, 48 years [IQR, 28–65]; 70.7% male; 95% with blunt mechanism; mortality, 3.2%), no discernable patterns in thrombin generation or MP concentration were observed over time. The peak height and MPs were significantly different from healthy volunteers and were 337 nM (IQR, 285–395) and 400/μL plasma (IQR, 211–772), respectively. Extreme (defined as highest or lowest 5%) values reflecting a possible "hypercoagulable state" (lag time ⩽ 1.98, peak height ≥ 486.2, ttPeak ⩽ 3.61, and total procoagulant MP ≥ 2, 278) were reached within 12 hours after acute trauma, while extreme values representing a possible "hypocoagulable state" (lag time ≥ 18.6, peak height ⩽ 17.8, and ttPeak ≥ 29.45) were not reached until 1 day to 3 days. CONCLUSION: Although there was no predictable pattern of coagulopathy observed in each patient after trauma, those who reached extreme values did so relatively early after injury. These findings should be taken into account when designing risk model tools involving coagulation laboratory parameters. LEVEL OF EVIDENCE: Epidemiologic study, level III. Abstract : Supplemental digital content is available in the text.